Current limitations and challenges in nanowaste detection, characterisation and monitoring. (September 2015) - Part, Florian; Zecha, Gudrun; Causon, Tim; Sinner, Eva-Kathrin; Huber-Humer, Marion
Highlights: First review on detection of nanomaterials in complex waste samples. Focus on nanoparticles in solid, liquid and gaseous waste samples. Summary of current applicable methods for nanowaste detection and characterisation. Limitations and challenges of characterisation of nanoparticles in waste. Abstract: Engineered nanomaterials (ENMs) are already extensively used in diverse consumer products. Along the life cycle of a nano-enabled product, ENMs can be released and subsequently accumulate in the environment. Material flow models also indicate that a variety of ENMs may accumulate in waste streams. Therefore, a new type of waste, so-called nanowaste, is generated when end-of-life ENMs and nano-enabled products are disposed of. In terms of the precautionary principle, environmental monitoring of end-of-life ENMs is crucial to allow assessment of the potential impact of nanowaste on our ecosystem. Trace analysis and quantification of nanoparticulate species is very challenging because of the variety of ENM types that are used in products and low concentrations of nanowaste expected in complex environmental media. In the framework of this paper, challenges in nanowaste characterisation and appropriate analytical techniques which can be applied to nanowaste analysis are summarised. Recent case studies focussing on the characterisation of ENMs in waste streams are discussed. Most studies aim to investigate the fate of nanowaste during incineration, particularly considering aerosol measurements; whereas, detailed studies focusing on the potential release of nanowaste during waste recycling processes are currently not available. In terms of suitable analytical methods, separation techniques coupled to spectrometry-based methods are promising tools to detect nanowaste and determine particle size distribution in liquid waste samples. Standardised leaching protocols can be applied to generate soluble fractions stemming from solid wastes, while micro- and ultrafiltration can be used to enrich nanoparticulate species. Imaging techniques combined with X-ray-based methods are powerful tools for determining particle size, morphology and screening elemental composition. However, quantification of nanowaste is currently hampered due to the problem to differentiate engineered from naturally-occurring nanoparticles. A promising approach to face these challenges in nanowaste characterisation might be the application of nanotracers with unique optical properties, elemental or isotopic fingerprints. At present, there is also a need to develop and standardise analytical protocols regarding nanowaste sampling, separation and quantification. In general, more experimental studies are needed to examine the fate and transport of ENMs in waste streams and to deduce transfer coefficients, respectively to develop reliable material flow models.